New Perspectives on the Immunopathogenesis and Treatment of Uveitis Associated With Vogt-Koyanagi-Harada Disease - Abu El-Asrar, Ahmed M.; Van Damme, Jo; Struyf, Sofie; Opdenakker, Ghislain (Frontiers in Medicine, 2021)
Uveitis associated with Vogt-Koyanagi-Harada (VKH) disease is a bilateral, chronic, granulomatous autoimmune disease associated with vitiligo, poliosis, alopecia and meningeal and auditory manifestations. The disease affects pigmented races with a predisposing genetic background. Evidence has been provided that the clinical manifestations are caused by a T-lymphocyte-mediated autoimmune response directed against antigens associated with melanocytes in the target organs. Alongside of T lymphocytes, autoreactive B cells play a central role in the development and propagation of several autoimmune diseases. The potential role of B lymphocytes in the pathogenesis of granulomatous uveitis associated with VKH disease is exemplified within several studies. The early initial-onset acute uveitic phase typically exhibits granulomatous choroiditis with secondary exudative retinal detachment and optic disc hyperemia and swelling, subsequently involving the anterior segment if not adequately treated. The disease eventually progresses to chronic recurrent granulomatous anterior uveitis with progressive posterior segment depigmentation resulting in “sunset glow fundus” appearance and chorioretinal atrophy if not properly controlled. Chronically evolving disease is more refractory to treatment and, consequently, vision-threatening complications have been recognized to occur in the chronic recurrent phase of the disease. Conventional treatment with early high-dose systemic corticosteroids is not sufficient to prevent chronic evolution. Addition of immunomodulatory therapy with mycophenolate mofetil as first-line therapy combined with systemic corticosteroids in patients with acute initial-onset disease prevents progression to chronic evolution, late complications, vitiligo and poliosis. Furthermore, patients under such combined therapy were able to discontinue treatment without relapse of inflammation. These findings suggest that there is a therapeutic window of opportunity for highly successful treatment during the early initial-onset acute uveitic phases, likely because the underlying disease process is not fully matured. It is hypothesized that early and aggressive immunosuppressive therapy will prevent remnant epitope generation in the initiation of the autoimmune process, the so-called primary response. B cell depleting therapy with the anti-CD20 monoclonal antibody rituximab is effective in patients with refractory chronic recurrent granulomatous uveitis. The good response after rituximab therapy reinforces the idea of an important role of B cells in the pathogenesis or progression of chronic recurrent uveitis associated with VKH disease.